Inclusivity at The Workplace: An Inquiry on The Environment of a Person with Special Needs in a Stem-Based Workplace - Jarina Peer; Lisa Ho (Jurnal Pendidikan Bitara UPSI, 2025)
People with special needs can be found increasingly in the workplace in recent years as there is greater acceptance of diversity, and inclusion. This research uses narrative inquiry to understand the factors/ conditions/ environment that promote or inhibit inclusiveness. This also gives an insight into the challenges faced by an individual who is presently in the laboratory-based workforce. Inclusion in the workplace is crucial for organizations that aim at creating a welcoming and supportive environment for all employees. Using in-depth semi-structured interviews, experiences of the subject were explored to gain a better understanding of the person’s life and work environment. The individual in this research case study has been living with special needs and is now actively working in a research lab in Singapore. Individual experiences seek to understand how various factors interact and contribute to the work environment. The emphasis will be on understanding contextually how different variables and aspects influence the person’s working life. The interview was transcribed and NVivo was used to organize and systematically code into themes or categories. The data was divided into various categories such as background, roles and perceptions of responsibilities, essential skills, support systems to accommodate workers’ needs, communication, and job satisfaction.